Front Cover: Photocatalytic Cycloadditions Enabled by a Lithium Perchlorate/Nitromethane Electrolyte Solution (Eur. J. Org. Chem. 6/2019). Issue 6 (5th February 2019) - Nagahara, Shingo; Wakamatsu, Hiroki; Okada, Yohei; Chiba, Kazuhiro
Abstract : The Front Cover shows a schematic impression of our photocatalytic cycloadditions involving carbon–carbon bond formations. Our methodology has employed lithium perchlorate/nitromethane electrolyte solution and this unique "platform stage" has enabled the photocatalytic cycloadditions in the absence of an external sensitizer. When starting materials are spotlighted on the platform stage by intensive 250 W UV lamp, several cycloadditions, including [2 + 2], [3 + 2], and [4 + 2] formats, take place effectively to give the corresponding cycloadducts in high yields, respectively. More information can be found in the Communication by K. Chiba et al.